2023
DOI: 10.1001/jamainternmed.2022.5890
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medicare Part B Spending on Discarded Drugs, 2017-2020

Abstract: This cross-sectional study quantifies trends in discarded drug spending since the onset of mandated reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Several analyses have suggested that the use of single-use vials for packaging cancer therapies is a large driver of infusion drug waste. 2,3 Oncologic therapies are often adjusted based on patient-specific factors such as body surface area (BSA) and renal function, so dose adjustment typically requires discarding some fraction of the vial to administer the correct dose. For example, if the patient-specific dose of a medication is 0.75 mg but the medication is manufactured in single-use 1-mg vials, 25% of that vial will be discarded after use.…”
mentioning
confidence: 99%
“…Several analyses have suggested that the use of single-use vials for packaging cancer therapies is a large driver of infusion drug waste. 2,3 Oncologic therapies are often adjusted based on patient-specific factors such as body surface area (BSA) and renal function, so dose adjustment typically requires discarding some fraction of the vial to administer the correct dose. For example, if the patient-specific dose of a medication is 0.75 mg but the medication is manufactured in single-use 1-mg vials, 25% of that vial will be discarded after use.…”
mentioning
confidence: 99%
“…1 Medication has simply become unaffordable: some patients may forgo recommended therapy altogether, while others who opt for the treatment may experience life-altering debt. 2,3 In this issue of JAMA Internal Medicine, O'Donoghue and colleagues 4 illuminated the prevalence and potential cost implications of discarding infused or injectable drugs. In the US, many injectable or infused drugs are packaged in single-use vials, with the dose dictated by the patient's body size and other factors.…”
mentioning
confidence: 99%
“…In this issue of JAMA Internal Medicine , O’Donoghue and colleagues illuminated the prevalence and potential cost implications of discarding infused or injectable drugs. In the US, many injectable or infused drugs are packaged in single-use vials, with the dose dictated by the patient’s body size and other factors.…”
mentioning
confidence: 99%